Makna Kafur dan Zanjabil dalam Surah Al-Insan Ayat 5 dan 17 (Analisis Penafsiran Al-Qurthubi dan Al-MiṣbᾹh) - Syahputri, Istiqomah Ayu (Lembaga Yasin AlSys, 2024)
This research discusses the meaning of Kafur and Zanjabil in Surah Al-Insan Verses 5 and 17 (Analysis of the Interpretation of Al-Qurthubi and Al-Miṣbāh). The problem that is the focus of this thesis research is how to interpret the meaning of kafur and zanjabil and how to analyze the interpretation of kafur and zanjabil in surah al-Insan verses 5 and 17 according to the interpretation of Al Misbah and Al Qurthubi. Meanwhile, the aim of this research is to find out the meaning of kafur and zanjabil and to understand the analysis of the interpretation of kafur and zanjabil in Surah Al-Insan verses 5 and 17 according to Al-Qurthubi and Al-Miṣbāh. The research is a type of library research, which uses data collection methods to browse and examine library materials, especially Tafsir Al-Miṣbāh and Al-Qurthubi as primary data, and relevant literature. The name ginger is only mentioned once in the Qur'an, namely in surah al-Insan verse 17, In heaven they are given a glass of drink (drink) mixed with ginger (zanjabil). Zanjabil is another name for ginger in Arabic. Therefore, in the Qur'an, Allah states that ginger is one of the ingredients that will be used as a drink mixture for the inhabitants of heaven, as a reward for all the good things they did while in this worldly life. Drinks from heaven and their categories are found in the verses of the Qur'an, namely drinks that are clear in color and smell delicious and taste delicious, called kafur drinks, found in surah al-Insan verse 5. There are so many pleasures in heaven, one of which is drink heaven, there are other unexpected pleasures that will be offered to devout human beings who will become residents of heaven.